Khanty, People of the Taiga : Surviving the 20th Century - Wiget, Andrew (Book collections on Project MUSE., 2011)
Drawing on nearly twenty years of fieldwork, as well as ethnohistory, politics, and economics, this volume takes a close look at changes in the lives of the indigenous Siberian Khanty people and draws crucial connections between those changes and the social, cultural, and political transformation that swept Russia during the transition to democracy. Delving deeply into the history of the Khanty-who were almost completely isolated prior to the Russian revolution-the authors show how the customs, traditions, and knowledge of indigenous people interact with and are threatened by events in the lar.